Good organizational practices to encourage women high-performance coaches in sports - Taylor, Damien; Hanlon, Clare; Dawson, Andrew (Frontiers in Sports and Active Living, 2023)
Women play a vital role in professional sport on and off the field. Globally, the dearth of women high-performance coaches in sport is a concern. For example, in Australia women represent 15% of high-performance coaches. One reason could be due to the lack of knowledge on good organizational practices that encourage women in this role and the overwhelming knowledge of practices focused on barriers for women high-performance coaches. The purpose of our research was to determine what good organizational practices exist to attract, develop, and retain women as high-performance coaches in Australia. Using a qualitative research design, semi-structured interviews were conducted with two study groups that comprised 16 women high-performance coaches and 13 senior managers from five National Sport Organizations (NSOs) in Australia. Data analysis was guided by practices that influenced the attraction, development, and retention of women high-performance coaches. Practically, findings revealed 12 good organizational practices and 31 associated recommendations to assist senior managers from NSOs in their quest to encourage women high-performance coaches in their sport. Theoretically, our research “reverses the lens” of the Ecological Intersectional Model (EIM) at the organizational level whereby the focus turns to good organizational practices rather than barriers for women high-performance coaches.